Genetic analysis of a novel antioxidant multi-target iron chelator, M30 protecting against chemotherapy-induced alopecia in mice - Young-Cheol Lim; Hyeongi Kim; Sang Moo Lim; Jin Su Kim (BMC Cancer, 2019)
Abstract Background Chemotherapy-induced alopecia has been well documented as a cause of distress to patients undergoing cancer treatment. Almost all traditional chemotherapeutic agents cause severe alopecia. Despite advances in the treatment of chemotherapy-induced alopecia, there is no effective treatment for preventing chemotherapy-induced alopecia. Methods In the present study, we investigated the potential role of a multi-target iron chelator, M30 in protecting against cyclophosphamide-induced alopecia in C57BL/6 mice implanted with an osmotic pump. M30 enhanced hair growth and prevented cyclophosphamide-induced abnormal hair in the mice. Furthermore, we examined the gene expression profiles derived from skin biopsy specimens of normal mice, cyclophosphamide-treated mice, and cyclophosphamide treated mice with M30 supplement. Results The top genes namely Tnfrsf19, Ercc2, Lama5, Ctsl, and Per1 were identified by microarray analysis. These genes were found to be involved in the biological processes of hair cycle, hair cycle phase, hair cycle process, hair follicle development, hair follicle maturation, hair follicle morphogenesis, regulation of hair cycle. Conclusion Our study demonstrates that M30 treatment is a promising therapy for cyclophosphamide-induced alopecia and suggests that the top five genes have unique preventive effects in cyclophosphamide-induced transformation.